2020
DOI: 10.1002/aenm.202002135
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Ionogel Electrolytes for Solid‐State Rechargeable Batteries

Abstract: Ionogels composed of ionic liquids and gelling solid matrices offer several advantages as solid‐state electrolytes for rechargeable batteries, including safety under diverse operating conditions, favorable electrochemical and thermal properties, and wide processing compatibility. Among gelling solid matrices, nanoscale materials have shown particular promise due to their ability to concurrently enhance ionogel mechanical properties, thermal stability, ionic conductivity, and electrochemical stability. These be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…Overall, while demonstrated here for solid‐state lithium‐ion batteries, this layered heterostructure ionogel electrolyte approach can likely be generalized to other emerging solid‐state battery technologies. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…Overall, while demonstrated here for solid‐state lithium‐ion batteries, this layered heterostructure ionogel electrolyte approach can likely be generalized to other emerging solid‐state battery technologies. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…IG materials retain the benefits of solid electrolytes (no leakage, dimensional stability, the potential for fabricating thinner electrolytes) while also maintaining the high ionic conductivity and electrochemical stability of ILEs. One family of IGs is based on having ionic liquids swelled into polymer matrices creating freestanding solids. Although IG electrolytes for LIB research are more common (primarily for nonflammable and high-temperature applications), there are some reports regarding IGs for SIBs. Singh et al, for example, reported an IG electrolyte consisting of an ionic liquid immobilized by poly­(ethylene oxide) .…”
Section: Introductionmentioning
confidence: 99%
“…In the amorphous region, lithium ions can better rely on the chain segment motion for transference. 49 Figure 3b shows the infrared spectrum of the polymer electrolyte. The spectral peaks at 1393 and 1370 cm −1 are δ s (OSO), and the spectral peak at 554 cm −1 is δ as (OSO).…”
Section: Resultsmentioning
confidence: 99%